Analogue Sochocky formulae for integral operators with additional logarithmic singularity - Kashevski, Vitold V. (Journal of the Belarusian State University. Mathematics and Informatics, 2018)
In this paper we prove the limit formulas for singular integrals of the form. Limit values of such integrals are expressed in terms of singular integral operators and also integral operators. As an application of these formulas derived additive representation for singular integrals. The formulas are derived in the article can be used for research and operators singular integral equations solutions.
Keywords: integral operators; singular integrals